2013
DOI: 10.1021/la403598s
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Water-Soluble HRP within Poly-N-isopropylacrylamide Microgel Particles for Use in Organic Media

Abstract: In the present work, the immobilization of enzymes within poly-N-isopropylacrylamide (p-NIPAM) microgels using the method of solvent exchange is applied to the enzyme horseradish peroxidase (HRP). When the solvent is changed from water to isopropanol, HRP is embedded within the polymer structure. After the determination of the immobilized amount of enzyme, an enhanced specific activity of the biocatalyst in isopropanol can be observed. Karl Fischer titration is used to determine the amount of water within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…In this study, laccase could be activated by a factor of 5,000. HRP could be activated by some 3,000‐fold upon immobilization in a p‐NIPAM microgel in isopropanol (Gawlitza et al, ), which is close to the here achieved 5,000‐fold activation achieved in by solubilization with POx‐IDA in chloroform. CT could be activated by a factor of up to 1,000 when solubilized by AOT in organic solvents (Paradkar & Dordick, ), while the activation of this enzyme immobilized on nanoporous silica glass in hexane reached a 110‐fold activity (P. Wang, Dai, Waezsada, Tsao, & Davison, ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this study, laccase could be activated by a factor of 5,000. HRP could be activated by some 3,000‐fold upon immobilization in a p‐NIPAM microgel in isopropanol (Gawlitza et al, ), which is close to the here achieved 5,000‐fold activation achieved in by solubilization with POx‐IDA in chloroform. CT could be activated by a factor of up to 1,000 when solubilized by AOT in organic solvents (Paradkar & Dordick, ), while the activation of this enzyme immobilized on nanoporous silica glass in hexane reached a 110‐fold activity (P. Wang, Dai, Waezsada, Tsao, & Davison, ).…”
Section: Discussionsupporting
confidence: 83%
“…However, they also work in organic solvents but are dramatically less active in their free form (Klibanov, ). The most common way to activate enzymes in organic media is to immobilize them on solid supports (Gawlitza, Georgieva, Tavraz, Keller, & von Klitzing, ; Mateo, Palomo, Fernandez‐Lorente, Guisan, & Fernandez‐Lafuente, ; Ruiz, Malavé, Felby, & Griebenow, ; Stepankova et al, ). This way the enzyme is accessible due to the large interface between the support and the solvent and at the same time stabilized.…”
Section: Introductionmentioning
confidence: 99%
“…Gawlitza et al reported that the particles still exhibit a water content of 46 % in the interior after transferring the particle from water to isopropanol. Their interpretation is the formation of a water cage within the particles, which is formed during the solvent exchange [34]. Wang et al reported a similar behavior [21].…”
Section: Shift In the Particle Size Minimum From Bulk To Adsorbed Parmentioning
confidence: 94%
“…Furthermore, microgel suspensions were studied as host media for proteins. In this approach, the network is swollen with the native buffer solution and protects the protein against denaturation and unfolding by a solvent [23,24,26].…”
Section: Introductionmentioning
confidence: 99%